THE ROLE OF INTEGRATED MARKETING COMMUNICATIONS ON PURCHASE DECISION (Survey on Creative Industry of Culinary Sub-Sector in Bandar Lampung) - Bunayya, Riana Pratiwi; Sugiono, Arif; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2021)
This research was aimed to find out the effect of advertising, sales promotion, and public relations on purchase decision consumer of Yussy Akmal. This research applies the explanatory type with quantitative approach. The population of this research were customer of Yussy Akmal. The sampling technique is purposive sampling with sample of 384 respondents. The data were obtained from questionnaire use likert scale. Data analysis in this research used multiple linear regression analysis with SPSS 26.0. Based on the results of research and data analysis show that advertising, sales promotion, and public relations simultaneously on purchase decision. While the partial test results of each variable show that advertising significantly affected on purchase decision, sales promotion significantly affected on purchase decision, and public relations significantly affected on purchase decision. Keywords : Advertising, Sales Promotion, Public Relations, and Purchase Decision